The Role of Digital Compotence, Digital Leadership, Digital Culture, And Religiosity, on Individual Creativity And Lecturers' Performance At Muhammadiyah University of Palopo - Sarmila; Rahmad Solling Hamid; Sofyan Samsuddin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the role of digital competence, digital leadership, digital culture, and religiosity on individual creativity and performance of lecturers at Muhammadiyah University of Palopo. Digital competence, digital leadership, digital culture, and religiosity are expected to influence lecturers' creativity in developing teaching materials and their performance in teaching and interacting with students. The research method used is quantitative with a survey approach, using questionnaires distributed to lecturers at Muhammadiyah University of Palopo. The results of the study indicate that digital competence has a significant positive impact on lecturers' creativity and performance. Digital leadership and digital culture also have a positive effect on creativity, while religiosity does not show a significant effect on lecturers' performance. This study contributes to the understanding of the factors that influence lecturers' creativity and performance in the digital era.